Income And Welfare Analysis of Rubber Farmers of Sarolangun Regency Jambi - Indonesia - Saidin Nainggolan; Yanuar Fitri; Vijai Hutasoit (RIRAI Publisher, 2022)
This study aims to analyze the income and welfare of rubber farmers. The research was conducted in the rubber production center of Sarolangun Regency with pauh subdistrict research locus, with sample villages of Karang Mendapo Village, Pauh Village and Semaran Village. The data usedn is primary data obtained by interview method using questionnaires. Sample withdrawal using Simple Random Sampling Metohd. The technique of determining the sample size uses the Slovinmethod. The sample size is 57 farmers. The research period is July - August 2021. Data analysis uses descriptive analysis, contingency tables and chi-square tests (x^₂). The results showed that most farmers have below average incomes. The main source of income for farmers comes from rubber farming. Rubber farmers' income groups are in the low to moderate category. The proportion of farmers' consumption expenditure is greater on food consumption (rice, side dishes), the proportion for non-food consumption is mostly for clothing. The welfare of farmers is in the low category. Differences in farmers' incomes cause significant differences in farmers' well-being. The degree of contingency of income on the welfare of farmers is in the moderate category. While the degree of income relationship of farmers with the welfare of farmers is positive and significant.